The ethical counselling in the sterility of couple. - Di Pietro, M.L.; Mancini, A.; Spagnolo, A.G. (Medicina e Morale, 2002)
The counselling to the sterile couple doesn't consist in the technical aspects of a clinical diagnosis only, but in the attention to the persons in their totality, particularly to their request of help in facing suffering given by the desire of a child and by the failures and disappointments that frequently go together the search of a solution. The Authors, analysing scientific literature, notice a nearly exclusive attention to the psychological aspect of the couple, considered separately from the counselling for the sterility. The Authors underline the counselling to the sterile couple in the Italian legislative perspective on the medical-assisted procreation: the proposal of law in matter dwells upon the effectiveness and the modalities of execution of the techniques, on their abortion percentage, on the risks for the woman and for the embryo, but also on the ethical consequences and on the costs. The consideration of the ethical aspects, even if little present in the medical literature, can not be neglected, being implicated in these procedures the conception of person and family and finalities recognised to the medicine. From the ethical point of view, it is not a neutral fact, for the couple and for the consultant, whose ethical convictions in this moment are faced. Close to such consideration, the Authors introduce personal experience developed in the Institute of Bioethics of the Catholic University of the Sacred Heart in Rome (Italy), from January 2000 to June 2002, on 25 couples from 30 to 40 years old. From the study the disappointment of the couples for a "poor" human behaviour of the physicians previously consulted and the lack of the information on the procedures emerge. Besides, the counselling had a phase from which has emerged, an incompleteness in the performed medical investigations and a scarce or wrong information from the expert on the post-diagnostic interventions, and a phase of dialogue between the ethical consultant and the couple. The Authors conclude that the management of the desire of paternity and maternity of the couple cannot put aside, because its complexity and peculiarity, from the cross-disciplinary integration of different and essential competencies: the competence of the gynaecologist, of the andrologist, of the experts in biology of the reproduction, in psychology and in bioethics.